On the origin of the water vapor continuum absorption within rotational and fundamental vibrational bands. (May 2017) - Serov, E.A.; Odintsova, T.A.; Tretyakov, M.Yu.; Semenov, V.E.
Abstract: Analysis of the continuum absorption in water vapor at room temperature within the purely rotational and fundamental ro-vibrational bands shows that a significant part (up to a half) of the observed absorption cannot be explained within the framework of the existing concepts of the continuum. Neither of the two most prominent mechanisms of continuum originating, namely, the far wings of monomer lines and the dimers, cannot reproduce the currently available experimental data adequately. We propose a new approach to developing a physically based model of the continuum. It is demonstrated that water dimers and wings of monomer lines may contribute equally to the continuum within the bands, and their contribution should be taken into account in the continuum model. We propose a physical mechanism giving missing justification for the super-Lorentzian behavior of the intermediate line wing. The qualitative validation of the proposed approach is given on the basis of a simple empirical model. The obtained results are directly indicative of the necessity to reconsider the existing line wing theory and can guide this consideration.